Technical-Vocational Livelihood Education: Emerging Trends in Contextualised Mathematics Teaching - Espinas, Alvin L.; Esponilla II, Francisco D.; Tolentino, Lean Karlo S.; Valenzuela, Ira C. (Journal of Technical Education and Training, 2020)
Technical-Vocational Livelihood Education (TVLE) Strategies and Indicators (S&Is) are the strategic procedures needed to come up with a well-informed contextualised learning instruction. This study is aimed at exploring the trends in Technical-Vocational Livelihood Education. The focus of this study is on soliciting relevant strategies and indicators (S&I) that can be utilised to develop a contextualised mathematics teaching module. S&Is in this study are consolidated from various experts in the field of curriculum contextualisation who were purposively selected from various regions representing the DepEd Manila, DepEd Mindoro, Marinduque, Romblon, and Palawan (MIMAROPA), DepEd Bicol region (Region 5), and DepEd Central Visayas (Region 7) recommended by the Department of Education (DepEd) Manila. Formal interviews and coding of consolidated experts’ experiences have passed through a qualitative thematic analysis to obtain a profound understanding of the strategies and indicators. After a thorough investigation of the information gathered, related studies, and theoretical reviews, the study resulted in the seven (7) stages of a contextualised mathematics teaching module such as 1) Planning, 2) Assessment of the curriculum guide and resources, 3) Collaboration and Consultative Meeting, 4) Crafting and Developing of the Contextualise Learning Modules/Lessons, 5) Implementation, 6) Monitoring, and 7) Evaluation and feedback. The first four (4) stages are the developmental phase cons Planning, Assessment, Collaboration, and Crafting of the working module (PACC). While, the remaining three stages to implement, monitor, and conducts of evaluation and feedback are on the validation phase. As module, the contextualised mathematics teaching can be utilised as a training guide for teachers in Technical-Vocational Livelihood Education strands of the K-12 curriculum. Further research may be conducted to validate the most appropriate modular approach in teaching specific subjects.